A sample of an integrated curriculum for grade five - Harati, Lina (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2004)
Significant attention is now being paid to the development of innovative curricula that are responsive to today's demands on students, and society. This paper's intent is to design a new curriculum stressing on the 21'st century learners needs, the learning process, the fragmented curriculum, its advantages and disadvantages, the new curriculum which is the integrated curriculum and its benefits and drawbacks, as well as the implementation information. This paper provides a yearly plan for the usage of the implemented curriculum using the books and curriculum objectives utilized at the school at which the researcher is a staff member. Lastly, a sample of lesson plans with activities for an integrated curriculum is provided. This paper tends to encourage the usage of this curriculum at the respective institution or any other educational institution in grade five since there is a need for continuous improvements as the demands are changing. This curriculum was designed in order to improve the learning of the students at Green School thus its books and curriculum's objectives were taken into consideration. However, this curriculum can be adapted to any other organization. Teachers can adjust the lesson plans accordingly, such as adding information about their country, or any new event. The provided curriculum is a guideline for those who are willing to adopt the integrated curriculum in their classrooms.
: Mémoire
Keywords: Curricula; Curriculum; Cycle primaire; Elementary Education